MENTAL HEALTH STATUS AND OCCUPATIONAL STRESS PREDICTORS AMONG HEALTHCARE WORKERS: A HOSPITAL-BASED CROSS-SECTIONAL STUDY FROM A TERTIARY CARE TEACHING HOSPITAL IN HARYANA, INDIA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Healthcare workers are exposed to multiple occupational stressors, including prolonged duty hours, high patient load, night-shift duties, inadequate sleep, workplace violence, and poor work-life balance. These factors contribute to adverse mental health outcomes such as stress, anxiety, and depressive symptoms. Objective: To assess mental health status and identify occupational stress predictors among healthcare workers at a tertiary care teaching hospital in Haryana, India. Methods: A hospital-based cross-sectional study was conducted from January 2025 to December 2025 among 400 healthcare workers selected by stratified random sampling. Doctors, nurses, interns, laboratory technicians, paramedical staff, and support staff were included. Data were collected using a structured questionnaire incorporating socio-demographic details, occupational characteristics, the Perceived Stress Scale-10 (PSS-10), Generalized Anxiety Disorder-7 scale (GAD-7), and Patient Health Questionnaire-9 (PHQ-9). Moderate-to-severe stress was defined as PSS-10 score ≥14. Clinically significant anxiety and depressive symptoms were defined as GAD-7 score ≥10 and PHQ-9 score ≥10, respectively. Data were analyzed using SPSS version 26.0. Chi-square test and multivariable logistic regression were applied to identify independent predictors of moderate-to-severe stress. Results: Among 400 participants, moderate-to-severe stress was observed in 248 (62.0%), clinically significant anxiety symptoms in 160 (40.0%), and clinically relevant depressive symptoms in 138 (34.5%). Stress prevalence was significantly higher among healthcare workers working >48 hours/week, night-shift workers, emergency/ICU staff, participants with poor sleep duration, and those exposed to workplace violence (p